2021
DOI: 10.1007/s11126-021-09957-0
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up Psychiatric Care and Risk of Readmission in Patients with Serious Mental Illness in State Funded or Operated Facilities

Abstract: Receipt of outpatient treatment within 30 days of discharge from psychiatric hospitalization is an established quality indicator; however, there is scant, mixed evidence as to whether it reduces the risk of readmission. We evaluated this question in patients hospitalized for schizophrenic, bipolar or depressive disorders using the Mental Health Treatment Episode Data Set (MH-TEDS), comprising patients in state-funded or -operated facilities and programs. We performed a 6-month, retrospective longitudinal cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Within 30 days after discharge from a psychiatric inpatient episode around one in six patients (17.3%) visited an office psychiatrist. This is more towards the lower end of the large range reported for visits to psychiatric outpatient services within 30 days post‐discharge in different health care systems, such as 9.1% for patients with schizophrenia, bipolar disorder and depression in state funded or operated mental health facilities in the USA (Hermer et al., 2022 ), 44% for schizophrenia in Canada (Kurdyak et al., 2018 ), 55.1% for any mental disorder in the national health service system in Italy (Donisi, Tedeschi, Salazzari, et al., 2016 ) and 85.1% for schizophrenia in Japan (Okumura et al., 2018 ). Such rates are not easily comparable, but it is of interest that in the Canadian study (Kurdyak et al., 2018 ) a comparison was performed between post‐discharge psychiatric and GP contacts, a comparison we were also able to perform.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within 30 days after discharge from a psychiatric inpatient episode around one in six patients (17.3%) visited an office psychiatrist. This is more towards the lower end of the large range reported for visits to psychiatric outpatient services within 30 days post‐discharge in different health care systems, such as 9.1% for patients with schizophrenia, bipolar disorder and depression in state funded or operated mental health facilities in the USA (Hermer et al., 2022 ), 44% for schizophrenia in Canada (Kurdyak et al., 2018 ), 55.1% for any mental disorder in the national health service system in Italy (Donisi, Tedeschi, Salazzari, et al., 2016 ) and 85.1% for schizophrenia in Japan (Okumura et al., 2018 ). Such rates are not easily comparable, but it is of interest that in the Canadian study (Kurdyak et al., 2018 ) a comparison was performed between post‐discharge psychiatric and GP contacts, a comparison we were also able to perform.…”
Section: Discussionmentioning
confidence: 99%
“…These results were obtained by using Cox regression with time‐dependent covariates, thereby avoiding the immortal time bias. This approach allowed to include also early re‐hospitalisations, which are a substantial fraction of total re‐hospitalisations, but are omitted in published registry‐based retrospective cohort studies on the association of early post‐discharge ambulatory contacts with psychiatric re‐hospitalisation (Beadles et al., 2015 ; Donisi, Tedeschi, Salazzari, et al., 2016 ; Hermer et al., 2022 ; Kurdyak et al., 2018 ; Lee et al., 2015 ; Marcus et al., 2017 ; Okumura et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective cohort study of schizophrenia and bipolar disorder found that outpatient follow-ups within 30 days after discharge were associated with slightly lower readmission risk . Another study revealed that patients who received timely follow-up visits had lower readmission rates in Japan and the US . Some studies examining the association between early outpatient follow-up after discharge and suicide risk have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Receiving timely follow-up care after hospital discharge is critical, given that patients with a recent hospitalization and their caregivers are particularly vulnerable during this time [8]. Lack of timely follow-up care when a patient transitions from the inpatient setting to outpatient care can result in medication discontinuation, rehospitalization, and other negative outcomes, such as poor symptom control, relapse, and impacts on families and caregivers [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%